2020
DOI: 10.1097/txd.0000000000001042
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing Rabbit Antithymocyte Globulin Induction in Kidney Transplantation (RETHINK): An Analysis of the North American Pediatric Renal Trials and Collaborative Studies (NAPRTCS) Registry

Abstract: Background. There is no consensus on rabbit antithymocyte globulin (rATG) dose used for induction immunosuppression in pediatric kidney transplants. We aimed to identify whether a lower rATG dose provides safe and effective immunosuppression compared with a higher dose. Methods. We retrospectively analyzed all first-time kidney transplant recipients (aged <21 y) in the North American Pediatric Renal Trials and Collaborative Studies registry since 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
(23 reference statements)
0
5
0
Order By: Relevance
“… 7 , 11 , 12 , 13 We have previously demonstrated a down trend in median cumulative rATG induction dose from 7.9 mg/kg (1998–2008) to 6.3 mg/kg (2009–2016) in the North American Pediatric Renal Trials and Collaborative Studies registry. 14 In that analysis, we did not identify a difference in patient and graft outcomes using a threshold of 5 rATG induction doses (7.5 mg/kg). Although data from Tsapepas et al.…”
Section: Discussionmentioning
confidence: 92%
“… 7 , 11 , 12 , 13 We have previously demonstrated a down trend in median cumulative rATG induction dose from 7.9 mg/kg (1998–2008) to 6.3 mg/kg (2009–2016) in the North American Pediatric Renal Trials and Collaborative Studies registry. 14 In that analysis, we did not identify a difference in patient and graft outcomes using a threshold of 5 rATG induction doses (7.5 mg/kg). Although data from Tsapepas et al.…”
Section: Discussionmentioning
confidence: 92%
“…A recent study using (NAPRTCS) registry data showed that 60% of pediatric kidney recipients in the US received ATG cumulative dose of <7.5 mg/kg. The study found no difference in time to acute rejection between recipients of <7.5 mg/kg dose and ≥7.5 mg/kg dose 38 . Special considerations for ATG dosing are given in Table 1 39 …”
Section: Atgmentioning
confidence: 93%
“…The study found no difference in time to acute rejection between recipients of <7.5 mg/kg dose and ≥7.5 mg/kg dose. 38 Special considerations for ATG dosing are given in Table 1. 39 Acute reactions during ATG administration are related to cytokine release syndrome.…”
Section: Dosing and Side Effectsmentioning
confidence: 99%
“…[12][13][14] However, recent studies have demonstrated that lower doses of r-ATG may be safer without loss of efficacy, including the use of a single dose. [15][16][17][18] Recently, a natural experiment conducted in our center demonstrated that, in adult kidney transplant recipients, the use of a single 3 mg/Kg r-ATG dose was associated with an 81% lower risk of acute rejection, without an increase in the risk of CMV infection compared to no induction. 19 Typically, pediatric kidney transplant recipients receive induction therapy with anti-IL-2R monoclonal antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…The use of r‐ATG has consistently shown higher efficacy for the prevention of acute rejection compared to anti‐IL‐2R monoclonal antibodies, 8–11 but concerns still exist regarding the increased risk of infections and cancer, especially at the initial doses of 1–1.5 mg/kg over 7–10 days 12–14 . However, recent studies have demonstrated that lower doses of r‐ATG may be safer without loss of efficacy, including the use of a single dose 15–18 …”
Section: Introductionmentioning
confidence: 99%